HARD SKILLS AND SOFT SKILLS: AN ANALYSIS OF COMPETENCIES AND SKILLS OF PROJECT MANAGERS - Alves Souza de Oliveira Veltrone, Milene; dos Santos, Sandyslaiza; Janaina Gomes de Oliveira, Mara (Revista Interface Tecnológica, 2024)
This paper aims to explore the importance of technical (hard skills) and interpersonal (soft skills) competencies for project managers. The methodology applied was qualitative research carried out with a sample of 30 project managers from companies in the industrial sector and medium-sized commercial companies, located in the city of São Carlos/SP. The results indicate that communication and leadership are necessary skills for managers to start projects within organizations and the skills to be developed are team management, deadline management, emotional intelligence and creativity.The difficulties faced were team engagement, conflict resolution and communication. The main challenges are communication, emotional intelligence and power of persuasion; in addition to the skills necessary for the role of manager, leadership, communication and organization. Therefore, it can be concluded that hard skills ensure technical performance, while soft skills guarantee efficient leadership and the ability to resolve conflicts, both necessary to guarantee organizational success.
Keywords: Technical skills; Social skills; Project Manager